Warisan Kuliner Randang Baluik sebagai Potensi Ekonomi di Nagari Pagaruyung Kabupaten Tanah Datar - Najmi, Najmi; Naldi, Hendra; Afriani, Rini; Silva, Ray; Nasution, Annisa Annida; Abianza, Erza (Jurnal Kronologi, 2024)
Nagari Pagaruyung which is located in Tanah Datar Regency is famous for producing rendang, especially "Randang Baluik" (Rendang Eel). On average, Nagari Pagaruyung women can cook this special food. Randang Baluik itself is made from eels and typical leaves that are used as a complement to its manufacture. The difference is that with other rendang such as meat rendang, eel rendang contains more typical leaves of eel rendang than the eel itself. The leaves for making rendang are very easy to find, especially in the Pagaruyung area. The process of making eel rendang is not much different from meat rendang, only the ingredients are different. The taste is also different. In addition, cooking randang baluik has become a hereditary tradition for the people of Pagaruyung and Tanah Datar in general. However, the community has not widely understood that randang baluik is an inherent cultural identity and as an economic source for the community. This is the researcher's finding and will find a solution for the community so that this cultural identity belongs to the community and is not lost to the times. The specific purpose of this research is to provide solutions to the government and the community about the importance of the cultural identity of randang baluik and as a source of additional income for the community. In addition, offering a solution, namely making Pagaruyung a country that produces randang baluik and later becomes a tourism potential, especially culinary tourism. This research will use a descriptive method of analysis using a historical approach. In addition, it also uses the literature method, namely by looking at sources such as previous studies that also discuss rendang and will also use the interview method with several sources.